STRESS URINARY INCONTINENCE: A TEN YEARS SYSTEMATIC REVIEW - Mahendra, Anton; Budiyono, Nur (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Stress urinary incontinence (SUI) and pelvic organ prolapse (POP) affect a substantial percentage of women, significantly impacting their quality of life. This review explores the prevalence, definitions, and pathophysiology of SUI, POP, and associated urinary incontinence, emphasizing the need for medical attention and offering insights into current treatment trends over the past 5 years. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 21 results. After looking at the titles and summaries, we found 9 papers that fit our criteria. At first, we excluded several articles because they were written in review style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included a retrospective observational study, prospective study, and randomized control trial. Conclusion: In this decade-long systematic review on stress urinary incontinence (SUI), notable findings include a 2.2 prevalence of SUI operations post-hysterectomy, persistent links between vaginal hysterectomy (VH) and SUI operations, and significant associations with preceding pelvic organ prolapse (POP), vaginal deliveries, laparoscopic hysterectomy (LH), and urinary incontinence (UI) visits. Combining pelvic floor muscle (PFM) strengthening with hip synergic muscle exercises improves daily urine loss frequency, while modifiable risk factors such as achieving an ideal body weight and preventing traumatic vaginal delivery are identified for SUI prevention. Cost analysis indicates that savings from avoiding unnecessary surgical treatments through urodynamic investigations (UDIs) in uncomplicated patients cover associated expenses, emphasizing the need to consider potential legal actions in a comprehensive cost assessment of negative externalities